SERVICE QUALITY GAP ANALYSIS (SERVQUAL) APPLIED IN THE CUSTOMER SERVICE QUALITY PROCESS IN A METALLURGICAL FOLLOWING COMPANY - de Oliveira, Michele Aparecida Maciel; de Medeiros, Luis Roberto (Revista Interface Tecnológica, 2022)
This article aimed to apply the SEVQUAL tool to measure customer satisfaction in terms of service quality. For that, it had as a theoretical nature based on the publication of books, monographs, and articles on the subject. The methodology also included a case study carried out in the company Industries Mechanical Panegossi -Ltda, located in the city of Matão - SP. Data collection for the case study was through a questionnaire applied in Google Forms with the caption, dissatisfied and satisfied directed to customers, from April to May 2022, whose principle was to obtain the opinion of each one about the satisfaction of the services provided by the company,  aiming at improving the quality of service applied in the SERVQUAL model. The results were all positive for the company studied. Where it was possible to conclude that, with the application of the questionnaire and the SEVQUAL analysis of the data, it is possible to affirm that the present analysis and research evidenced the importance of measuring the quality of the services provided.
Keywords: Customer Satisfaction; Quality; Servqual